Pengukuran User Experience Platform Otomasi Proses berbasis Low Code Menggunakan UEQ - Falih, Noor; Supangkat, Suhono Harso; Lubis, Fetty Fitriyanti; Prabowo, Okyza Maherdy (APIC, 2023)
This study analyzes the user experience of a Low Code-based Process Automation Platform to enhance efficiency, productivity, and accuracy in business processes. In this study, an analysis of user experience was carried out using a modified long version of the User Experience Questionnaire (UEQ), consisting of six scales: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Based on the evaluation of the 26 items from the UEQ, the dependability and novelty scales scored the lowest compared to the other scales. Therefore, it is necessary to improve the aspects related to these two scales in order to enhance the platform's role in improving the holistic user experience of the platform.